Evaluation of geohydraulic response properties of hydrogeological units in Littoral hydro-lithofacies in Uyo, Southern Nigeria - Johnson C. Ibuot; Daniel N. Obiora; Nyakno J. George (Applied Water Science, 2023)
Abstract Aquifer geohydraulic response properties are important parameters in groundwater resource management and exploitation. However, geohydraulic properties in the study area is sketchy and due to wildcat drilling. This practice, which leads to inadequate inventory of groundwater parameters, deprived the area of efficient exploitation, monitoring and management of groundwater resources. This study is aimed at evaluating the geo-hydraulic response properties of hydrogeological units in littoral hydro-lithofacies in Uyo, Southern Nigeria. Vertical electrical sounding (VES) technique was carried out, and a total of fifteen geoelectric soundings were obtained using IGIS Resistivity metre model SSR-MP-ATS and its accessories employing Schlumberger electrode configuration. The interpreted data give sets of geoelectric curves from which the aquifer resistivity and thickness were determined. The results reveal the aquifer bulk resistivity ranging from 23.4 to 1306.2 Ωm with an average of 347.99 Ωm, while aquifer thickness spanned from 7.4 to 56.3 m. The formation factor, fractional porosity and transmissivity ranged from 2.41 to 12.52, 0.20 to 0.46, and 0.001 to 0.037m2/s, respectively. The formation tortuosity also ranged from 1.05 to 1.58; longitudinal conductance ranged from 0.020 to 1.004 Ω−1; and transverse resistance ranged from 549.90 to 69,097.98 Ωm2. These parameters were contoured, and their variations are displayed on the contour maps generated. The graphs plotted showed strong correlation coefficient and earth response function that can be used in modelling the aquifer repositories in areas with similar geomaterials. The results of this study indicate that the survey area has a good prospect for groundwater accumulation, and the results can be useful in installing matching hydraulic pumps in boreholes in the survey area.